Kinematic differences in upper limb joints between flat and topspin forehand drives in competitive male tennis players. Issue 2 (3rd March 2020) - Genevois, Cyril; Reid, Machar; Creveaux, Thomas; Rogowski, Isabelle
Abstract: The topspin tennis forehand drive has become a feature of modern game; yet, as compared to the serve, there has been little research analysing its kinematics. This is surprising given that there is considerably more variation in the execution of the topspin forehand. Our study is the first to examine the amplitude of upper limb joint rotations that produce topspin in the forehand drives of 14 male competitive tennis players using video-based motion analysis. Humerothoracic abduction (- )/adduction (+), extension (- ) /flexion (+), and external (- )/internal (+) rotation, elbow extension (- ) /flexion (+) and forearm supination (- )/pronation (+), wrist extension (- )/flexion (+) and ulnar (- )/radial (- ) deviation were computed. Our findings revealed that the generation of topspin demanded more humeral extension and forearm pronation but less humeral internal rotation angular displacement during the forwardswing. The follow-through phase of the topspin shot was characterised by greater humeral internal rotation and forearm pronation, and reduced humeral horizontal adduction when compared to the flat shot. This study provides practitioners with a better understanding of the upper limb kinematics associated with the topspin tennis forehand drive production to help guide skill acquisition interventions and physical training.